Perilaku Pendakian Gunung di Masa Kenormalan Baru (Analisis Perspektif Pendaki Gunung di Jawa Barat) - Syifaa Novianti; Fauziah Farhah Zamilah; Tomy Andrianto (Journal of Event, Travel and Tour Management, 2022)
The aim of this study is to understand the behavior of mountaineer during the new normal of the Covid-19 pandemic. Although during the pandemic, mountaineering is still a favorite tourist outdoor activity to avoid crowds. The mountain attraction operator also claims to have implemented strict health protocols. However, only a few or none of studies discussing the mountaineer’s behavior during new normal. This study uses a qualitative method by conducting semi-structured interviews from 16 mountaineers in June-July 2021. The data were processed through several stages, namely reducing data, improving the appearance, one-stage coding and conducting content analysis. As the result, mountaineers tend to ignore health protocols, especially removing masks and rarely washing their hands during moountaineering. However, mountaineers mostly able to keep their distance and still pay attention to the environmental sustainability. In addition, mountaineers appreciate the operator which have implemented the CHSE procedures (cleanliness, health, safety and environmental sustainability) especially at the starting point of the mountaineering.